Konsep al-Qiyas al-Usuli dan al-Qiyas al-Mantiqi dalam Pendalilan Akidah: The Concepts of al-Qiyas al-Usuli and al-Qiyas al-Mantiqi in Theological Reasoning - Wahab, Muhammad Rashidi; Hamat, Mohd Fauzi; Azmi, Mohd Faizul (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
Logical reasoning is one of the main source of the theological discussion besides al-Qur’an and Hadith. The position of logical reasoning was recognized by scholars of Ahl al-Sunnah wa al-Jama’ah to generate confidence of belief in Allah SWT. Al-qiyas al-usuli and al-qiyas al-mantiqi are concepts of al-qiyas which is part of logical reasoning. The past literatures indicate that the polemic occur between the both concept of al-qiyas because of misunderstanding about equations and differences between al-qiyas al-usuli and al-qiyas al-mantiqi. Moreover, others thought al-qiyas al-usuli applies only in fiqh and al-qiyas al-mantiqi only in theology. This study employs content analysis methodology to examine the concepts and position of al-qiyas al-usuli and al-qiyas al-mantiqi in theological reasoning. This study found that the both concept can be applied in theological discussion and have capability to generate conclusions and beliefs.